2016
DOI: 10.3329/bvet.v32i2.30611
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of silver-curcumin on wound healing in rabbits

Abstract: Curcumin, a natural product obtained from the rhizomes of Curcuma longa, is used traditionally in prevention of wound infection. To determine the effects of silver and curcumin combination on surgical wound healing, a study was conducted in rabbits. A total of 32 surgical wounds were created in 16 rabbits in four groups. Information was recorded from Day 0 to Day 42 postoperatively. Swelling area of wound, elevation of suture line from the skin surface, width of sutured area and contraction length were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In another study, faster healing was observed in treatment with silver in wound treatment trials with turmeric and silver nanoparticles in rabbits (Islam et al ,2015). In the treatment of melanoma usage: It has been emphasized that nanoparticles are effective in the absorption and distribution of drugs in the chemotherapy phase in melanoma and that more studies on cell targeting and distribution are needed (Naves et al, 2017).…”
Section: Allergen-specific Immunotherapy (Asit) Usagementioning
confidence: 99%
“…In another study, faster healing was observed in treatment with silver in wound treatment trials with turmeric and silver nanoparticles in rabbits (Islam et al ,2015). In the treatment of melanoma usage: It has been emphasized that nanoparticles are effective in the absorption and distribution of drugs in the chemotherapy phase in melanoma and that more studies on cell targeting and distribution are needed (Naves et al, 2017).…”
Section: Allergen-specific Immunotherapy (Asit) Usagementioning
confidence: 99%